Athenian philosopher and English convert to the accusers. Apologia pro vita sua John H. Newman and The Apology of Socrates by Plato as examples of apology pro vita sua - Artemiuk, Przemysław (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
The new apologia, as well as contemporary fundamental theology, considers the work of Plato as the base. It is Socrates who emphasizes „unchanging ideas of moral significance.” Therefore, later apologists, such as Justin, Clement of Alexandria, Origen or Augustine, and, in more recent times, J.H. Newman and G.K. Chesterton, defending their own arguments in a dispute with the world, eagerly looked at the Athenian philosopher, who was the first one to use pro vita sua apologia. It was because he knew that there were non-negotiable things that could not be changed by any political system. In the presented article, the author examines what the phenomenon of Socrates’ defense consists of and why it has such a strong influence. Trying to find answers to these questions, he first analyzes the work of Plato, and then goes back to the nineteenth-century Apologia pro vita sua by J.H. Newman, which mimics the defense of the Athenian thinker. The author presents the conclusions drawn from the analyzed works from the viewpoint of fundamental theology.